Ketoprofen as an emerging contaminant: occurrence, ecotoxicity and (bio)removal - Tyumina, Elena; Subbotina, Maria; Polygalov, Maxim; Tyan, Semyon; Ivshina, Irina (Frontiers in Microbiology, 2023)
Ketoprofen, a bicyclic non-steroidal anti-inflammatory drug commonly used in human and veterinary medicine, has recently been cited as an environmental contaminant that raises concerns for ecological well-being. It poses a growing threat due to its racemic mixture, enantiomers, and transformation products, which have ecotoxicological effects on various organisms, including invertebrates, vertebrates, plants, and microorganisms. Furthermore, ketoprofen is bioaccumulated and biomagnified throughout the food chain, threatening the ecosystem function. Surprisingly, despite these concerns, ketoprofen is not currently considered a priority substance. While targeted eco-pharmacovigilance for ketoprofen has been proposed, data on ketoprofen as a pharmaceutical contaminant are limited and incomplete. This review aims to provide a comprehensive summary of the most recent findings (from 2017 to March 2023) regarding the global distribution of ketoprofen in the environment, its ecotoxicity towards aquatic animals and plants, and available removal methods. Special emphasis is placed on understanding how ketoprofen affects microorganisms that play a pivotal role in Earth’s ecosystems. The review broadly covers various approaches to ketoprofen biodegradation, including whole-cell fungal and bacterial systems as well as enzyme biocatalysts. Additionally, it explores the potential of adsorption by algae and phytoremediation for removing ketoprofen. This review will be of interest to a wide range of readers, including ecologists, microbiologists, policymakers, and those concerned about pharmaceutical pollution.